2010
DOI: 10.3168/jds.2009-2853
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein concentration and protein–saliva interactions in the astringency of whey proteins at low pH

Abstract: Whey protein beverages are adjusted to pH <4.5 to enhance clarity and stability, but this pH level is also associated with increased astringency. The goal of this investigation was to determine the effects of protein concentration on astringency and interactions between whey and salivary proteins. Whey protein beverages containing 0.25 to 13% (wt/wt) beta-lactoglobulin and 0.017% (wt/wt) sucralose at pH 2.6 to 4.2 were examined using descriptive sensory analysis. Controls were similar pH phosphate buffers at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 47 publications
4
57
0
Order By: Relevance
“…Therefore, if whey proteinesaliva interactions determine astringency, the in vitro model should relate better to astringency. Kelly et al (2010) found no obvious relationship between astringency and turbidity on mixing whey proteins with saliva in a 1:1 ratio. In contrast, simple correlations have been observed between astringency and turbidity on mixing polyphenols with saliva (Monteleone et al, 2004).…”
Section: Comparison Of In Vitro Mouth Models To Published Astringencymentioning
confidence: 82%
See 3 more Smart Citations
“…Therefore, if whey proteinesaliva interactions determine astringency, the in vitro model should relate better to astringency. Kelly et al (2010) found no obvious relationship between astringency and turbidity on mixing whey proteins with saliva in a 1:1 ratio. In contrast, simple correlations have been observed between astringency and turbidity on mixing polyphenols with saliva (Monteleone et al, 2004).…”
Section: Comparison Of In Vitro Mouth Models To Published Astringencymentioning
confidence: 82%
“…It is notable, that as the concentration of whey protein in an acidic beverage is increased, astringency does not greatly increase (Childs & Drake, 2010;Kelly et al, 2010). For example, Kelly et al (2010) found that astringency reached a maximum in beverages containing 4e5% (w/w) protein, and did not increase with higher protein concentrations.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Soukoulis, et al [25] reported that pH affected the flavor of yogurt when WPC were added in the formulation. Furthermore, other authors found that higher whey protein content in yogurts increased the buffering capacity in the product and also influenced the flavor perception [24,26,27].…”
Section: Experimental Designmentioning
confidence: 97%